Role of Lectin-Like Oxidized Low-Density Lipoprotein Receptor-1 in Inflammation and Pathogen-Associated Interactions - Sarah Truthe; Tilman E. Klassert; Stefan Schmelz; Danny Jonigk; Wulf Blankenfeldt; Hortense Slevogt (Karger Publishers, 2024)
Background: Lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) is known as a major receptor for oxidized low-density lipoproteins (oxLDL) and plays a significant role in the genesis of atherosclerosis. Recent research has shown its involvement in cancer, ischemic stroke, and diabetes. LOX-1 is a C-type lectin receptor and is involved in the activation of immune cells and inflammatory processes. It may further interact with pathogens, suggesting a role in infections or the host's response. Summary: This review compiles the current knowledge of potential implications of LOX-1 in inflammatory processes and in host-pathogen interactions with a particular emphasis on its regulatory role in immune responses. Also discussed are genomic and structural variations found in LOX-1 homologs across different species as well as potential involvements of LOX-1 in inflammatory processes from the angle of different cell types and organ-specific interactions. Key Messages: The results presented reveal both similar and different structures in human and murine LOX-1 and provide clues as to the possible origins of different modes of interaction. These descriptions raise concerns about the suitability, particularly of mouse models, that are often used in the analysis of its functionality in humans. Further research should also aim to better understand the mostly unknown binding and interaction mechanisms between LOX-1 and different pathogens. This pursuit will not only enhance our understanding of LOX-1 involvement in inflammatory processes but also identify potential targets for immunomodulatory approaches.